(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article discusses strategies that are helpful in developing reading and writing skills. The need to take into account the age characteristics of students in the development of reading and writing skills is explained on the basis of important evidence. Rather, the activities’ integration and this is a crucial word reinforces these languages’ inherent interconnectedness. What distinguishes integration is a common objective that forms the basis of all actions. All activities listening, speaking, reading, writing, or any combination of these help an integrated classroom effectively accomplishes its objectives